Efficacy of Intragastric Balloon Placement and Botulinum Toxin Injection in Bariatric Endoscopy. Issue 6 (December 2020) - Kanlioz, Murat; Ekici, Uğur; Tatli, Faik; Karatas, Turgay
Abstract : Background: To evaluate the results obtained from the combination of intragastric botulinum toxin A (IGBTA), intragastric balloon (IGB), and IGBTA(+)IGB in the treatment of obesity. Materials and Methods: Three separate treatment groups were set up. IGBTA, IGB, and IGBTA(+)IGB were administered to Group 1, 2, and 3, respectively. The body mass indexes (BMI) of patients were measured before and 6 months after the treatment. The intragroup and intergroup treatment results have been evaluated. P <0.05 was considered significant. Results: The mean BMI decreased by 1.6 kg/m 2 in 40 patients who received IGBTA in group 1 ( P <0.001), 3.95 kg/m 2 in 42 patients who received IGB in group 2 ( P <0.001), and 4.9 kg/m 2 in 39 patients who received IGBTA and IGB in group 3 ( P <0.001) after 6 months of treatment. The intolerance because of the application was the highest in group 3, followed by group 2. Conclusion: The treatment was most successful in group 3 followed by group 2 and group 1, respectively. The authors recommend the group 3 treatment, provided that nausea, vomiting, and flatulence have a high index of probability in such a treatment. However, when deciding between group 1 and group 2 treatments, the authors recommend opting for group 2 treatment that shows to be more efficient.